2009
DOI: 10.1093/abbs/gmp049
|View full text |Cite
|
Sign up to set email alerts
|

<italic>BMPRII</italic> is a direct target of miR-21

Abstract: MicroRNAs (miRNAs) are a type of small non-coding RNAs that regulate cognate mRNA expressions at the post-transcriptional stage. Although several miRNAs are known to be involved in various biological processes, including developmental timing, patterning, embryogenesis, differentiation and organogenesis, growth control, and apoptosis, many target genes and the functions of most miRNAs are still unclear. Since there is only a partial complementarity between miRNAs and their targets in animal cells, it is difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…First, bioinformatics predictions suggested that PTX3, HAS2 and PTGS2 are not the target genes of miR-375, and miR-375/ BMPR2 does not directly regulate PTX3, HAS2, and PTGS2. The reason for decreased levels of PTX3, HAS2 and PTGS2 may be because miR-375 triggers a large number of cells to undergo apoptosis, which is also supported by some previous reports [17, 19, 25] and our follow-up experiments (Fig. 7).…”
Section: Discussionsupporting
confidence: 91%
“…First, bioinformatics predictions suggested that PTX3, HAS2 and PTGS2 are not the target genes of miR-375, and miR-375/ BMPR2 does not directly regulate PTX3, HAS2, and PTGS2. The reason for decreased levels of PTX3, HAS2 and PTGS2 may be because miR-375 triggers a large number of cells to undergo apoptosis, which is also supported by some previous reports [17, 19, 25] and our follow-up experiments (Fig. 7).…”
Section: Discussionsupporting
confidence: 91%
“…These mutations prevent the activation of caspases-8, -9, and -3 and result in the derepression of Bcl2. In human prostate carcinoma cells, Qin et al [49] recently showed that through direct targeting of four predicted sites within BMPR2 mRNA, miR-21 down-regulates levels of BMPR2.…”
Section: Mir-21 Targetsmentioning
confidence: 99%
“…Specifically, miR-21 has been found to be overexpressed in numerous different solid tumors. Altered miR-21 has been found to be associated with the proliferation, invasion and apoptosis of malignant cells by targeting and downregulating a number of tumor suppressors, including PTEN (6,7), programmed cell death 4 (PDCD4) (8)(9)(10)(11), bcl-2 and tropomyosin l (TPM1) (12)(13), bone morphogenetic protein receptor II (BMPRII) (14) and sprouty 2 (SPRY2) (15). These findings imply that miR-21 plays a fundamental role in malignant behavior and transformation.…”
Section: Introductionmentioning
confidence: 99%